Plasma homocysteine and B vitamins levels in Nigerian children with nephrotic syndrome (2014)
Introduction: Available data on plasma homocysteine level in patients with nephrotic syndrome (NS) are controversial with increased, decreased and unchanged values reported. Therefore, plasma homocysteine and serum B vitamins in Nigerian children with NS were assessed in this study Methods: Fasting blood samples were analysed for plasma homocysteine, serum folate and B vitamins in 42 children with NS and 42 age and sex-matched healthy controls in this case control study. Data were compared between NS and control using t test and Chi square. Relationships were tested with regression analysis with p set at 0.05. Results: Prevalence of hyperhomocysteinaemia, low folate and cyanocobalamin in NS was 57.1%, 14.3% and 9.5% respectively. The mean homocysteine level was significantly higher in NS than control (11.3±2.6μmol/L versus 5.5±2.3μmol/L). Also, NS had lower folate and cyanocobalamin than control: 9.1±3.9ng/mL versus 11.2±3.1ng/dL and 268.5±95.7pg/mL versus 316±117.2pg/mL respectively. Weak but significant correlation between homocysteine and serum albumin (r = 0.347), folate (r = -0.607) and vitamin B12 (r = -0.185) were found in the NS group. Significant relationship was also found between homocysteine and vitamin B12 (ß = -0.64, 95% CI = -1.20, -0.08) after controlling for folate and vitamin B6 levels. Conclusion: Clinically important hyperhomocysteinaemia and low B vitamins occur in Nigerian children with nephrotic syndrome. This data suggest that potential usefulness of folate and vitamin B supplementation for reducing high homocysteine levels in nephrotic syndrome need to be further investigated